Emerging strategies from the teaching of photosynthesis for the transfer of environmental culture (Agroindustria, Sociedad y Ambiente, 2021)
This article was outlined from the elements that make up the theoretical construct configured from the findings that emerged during the research activity that is in its final phase as a doctoral thesis on the approach of an environmental culture in the socio-educational context of the secondary education level. in the state of Cojedes, for which a qualitative research of an interpretive paradigm with a phenomenological method was carried out. It was formulated as an intention to glimpse the emerging lines in the transfer of knowledge for the configuration of a new environmental culture. To achieve this purpose, a semi-structured interview was applied to the versioners with a teacher and student profile, which was applied in a public and private high school. The findings include that the educational platform must be configured with the technological components that provide innovation to the educational process both in the application of ICT and social capital networks that strengthen learning for the respective adaptation of the student to their realities, the teacher who is responsible for the teaching process and subject in this research that allowed me to demonstrate the tools that he makes available during his work to infuse his students with the necessary information about the natural process of photosynthesis and which currently must seek more dynamic tools and rely on new technologies and approaches to awaken the interests of the student
Keywords: Emerging strategies; teaching of photosynthesis; environmental culture